DARI HOMOTOPIA KE HETEROTOPIA PERUBAHAN KONSTRUKSI RUANG DALAM FIKSI INDONESIA - -, Pujiharto (Diksi, 2008)
This article is about a study aimed at (1) knowing whether there has been achange from epistemological to ontological domination in Indonesian fiction and(2) the repertoire of ontological foregrounding strategies that forms an organizedsystem called the postmodernism poetics of Indonesian fiction and especiallythose related to space.To attain its aim, the study applies the postmodernism theory. The theoryproposes that the change from modern to postmodern fiction is signaled by achange from epistemological to ontological domination in fiction. Furthermore, toknow how the repertoire of postmodernist foregrounding strategies operates inIndonesian fiction, the heterocosm theory is suggested.The result of the study indicates that a change from epistemological toontological domination has occurred in Indonesian fiction. In Indonesian fiction, avariety in the repertoire of ontological foregrounding strategies related to spaceconstruction has been found. The strategies are interpolation, misattribution,juxtaposition, and migration.Keywords: epistemological, ontological, strategy